ANALISIS KEPUTUSASAAN MAHASISWA SEMESTER AKHIR DALAM MENGERJAKAN SKRIPSI - Salwa Ramadhina; Hayu Stevani; Hilwa Zahrina; Nathania Tsany Jauza; Syarah Fathiah Rustamiza; Awaludin Syadad Al-Mafruh; Alisa Kusuma Wardhani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Scientific research is an important element in the advancement of higher education, representing the university's commitment to teaching, research, and community service. Thesis, as the final stage of undergraduate education, requires students to compose a scholarly work as a requirement for graduation, but this process is not free from various challenges, including writing difficulties, lack of motivation, and personal constraints. Kierkegaard provides an in-depth perspective on despair by identifying several aspects, such as awareness, possibility and inevitability, imagination, relationship with God, and understanding. The purpose of this study is to find out the causes of despair of final semester students in doing their final project. The subjects in this study were final semester students of Prof. Dr. HAMKA Muhammadiyah University who were working on their thesis. The method used in this research is qualitative survey research method. The data collection techniques used in this study were interviews, observation, and documentation. The findings in this study show that students have self-awareness related to the experience of hopelessness experienced and emphasize the importance of personal responsibility in overcoming challenges. In overcoming hopelessness, UHAMKA students show diverse responses by relying on time management, social support, and maintaining spiritual relationships. In conclusion, UHAMKA students managed to overcome these challenges resiliently, supported by strong social support and deep spiritual connections, reflecting a complex personal and academic journey.